2019
DOI: 10.1093/cid/ciz1088
|View full text |Cite
|
Sign up to set email alerts
|

African Multi-Site 2-Year Neuropsychological Study of School-Age Children Perinatally Infected, Exposed, and Unexposed to Human Immunodeficiency Virus

Abstract: Background Children living with human immunodeficiency virus (HIV) are at neuropsychological risk for cognitive and motor dysfunction. However, few prospective, multi-site studies have evaluated neuropsychological outcomes longitudinally among perinatally infected African children who received early antiretroviral treatment (ART). Methods We enrolled 611 children aged 5 to 11 years at 6 sites (South Africa [3], Zimbabwe, Mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 26 publications
3
22
0
Order By: Relevance
“…Perinatally HIV-infected (pHIV) children consistently present with a higher prevalence of neurological impairment than infected adults despite controlled viremia with ART ( Cohen et al 2015 ; Phillips et al 2016 ). Neuropsychological evaluations suggest that pHIV children display deficits in planning/reasoning, cognitive ability, motor proficiency, working memory, attention/impulsivity, IQ, and executive function ( Boivin et al 2019 ; Cohen et al 2015 ; Nichols et al 2016 ; Phillips et al 2016 ; Van den Hof et al 2019b ). The neurodevelopmental sequelae of pHIV children have long-term consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Perinatally HIV-infected (pHIV) children consistently present with a higher prevalence of neurological impairment than infected adults despite controlled viremia with ART ( Cohen et al 2015 ; Phillips et al 2016 ). Neuropsychological evaluations suggest that pHIV children display deficits in planning/reasoning, cognitive ability, motor proficiency, working memory, attention/impulsivity, IQ, and executive function ( Boivin et al 2019 ; Cohen et al 2015 ; Nichols et al 2016 ; Phillips et al 2016 ; Van den Hof et al 2019b ). The neurodevelopmental sequelae of pHIV children have long-term consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, child development is influenced by a myriad of socio‐environmental factors affecting children raised in families affected by HIV, which may become more evident as the child ages. An African multisite study of HEI school‐age children on suppressive ART initiated in early childhood concluded the children as being at significant neuropsychological risk, even with ART and medical support (Boivin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…ages. An African multisite study of HEI school-age children on suppressive ART initiated in early childhood concluded the children as being at significant neuropsychological risk, even with ART and medical support (Boivin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The Test of Variables of Attention (TOVA. Version 8.0) was also administered to all subjects as it has been used with sub-Saharan African populations across a wide range of 1 www.Cogstate.com studies (Bangirana et al, 2015;Boivin et al, 2019). The TOVA has several advantages because it uses visual stimuli, measures response times precisely (±1 m sec), is language-and culturefree, and has a history of use in resource-challenged areas (Ruel et al, 2012).…”
Section: Methodsmentioning
confidence: 99%